The effect of aspirin therapy on the plasma renin activity in myocardial infarction - M.H Ansari; F GHavam; A Rashidi; K Etemad (Journal of Kerman University of Medical Sciences, 1995)
In this study, the changes of renin system activity and the effects of aspirin therapy on the plasma renin activity ( PRA) in myocardial infarction were investigated. Fifty nine patients with myocardial infarction were selected. By suppressed in the former group which was statistically significant ( p<0.01).